Publisher Correction: Tissue clearing and its applications in neuroscience - Ueda, Hiroki R; Ertürk, Ali; Chung, Kwanghun; Gradinaru, Viviana; Chédotal, Alain; Tomancak, Pavel; Keller, Philipp J (Nature reviews. Neuroscience, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.